Kilconnell Franciscan Friary, west exterior wall, door - O'Donovan, Danielle (My University, 2009)
West door jamb, arch and hood moulding. Moulding from intrados comprises: quadrant, hollow chamfer, right-angled rebate, quadrant, hollow chamfer. The hood, from extrados to intrados comprises: frontal fillet, hollow chamfer, quadrant.
West door
Keywords: quadrant; Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Architecture, Franciscan; Gothic doorways; Late Medieval; moldings, hollow; roll moldings; hood moldings